2011
DOI: 10.1093/eurpub/ckr066
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of criteria to select projects for funding in the EU health programme

Abstract: The study shows the successful development and validation of criteria to evaluate EU health project grant proposals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Sub-optimal projects are financed due to unexpected circumstances that affect the budget allocation, mistakes in calculation, planning error, and strategic misrepresentation of target benefits. Van den Broucke et al 30 reported on the assessment of criteria to select projects for funding in the EU health programme. The key element in selecting the most valuable projects in assuring the EU Health Programme's quality is the evaluation process according to quality standards.…”
Section: Budget Constraintmentioning
confidence: 99%
“…Sub-optimal projects are financed due to unexpected circumstances that affect the budget allocation, mistakes in calculation, planning error, and strategic misrepresentation of target benefits. Van den Broucke et al 30 reported on the assessment of criteria to select projects for funding in the EU health programme. The key element in selecting the most valuable projects in assuring the EU Health Programme's quality is the evaluation process according to quality standards.…”
Section: Budget Constraintmentioning
confidence: 99%